Association of cognitive function and liability to addiction with childhood herpesvirus infections: A prospective cohort study. (19th April 2017) - Vanyukov, Michael M.; Nimgaonkar, Vishwajit L.; Kirisci, Levent; Kirillova, Galina P.; Reynolds, Maureen D.; Prasad, Konasale; Tarter, Ralph E.; Yolken, Robert H.
Abstract: Liability to substance use disorder (SUD) is largely nonspecific to particular drugs and is related to behavior dysregulation, including reduced cognitive control. Recent data suggest that cognitive mechanisms may be influenced by exposure to neurotropic infections, such as human herpesviruses. In this study, serological evidence of exposure to human herpesvirus Herpes simplex virus Type 1 (HSV-1), cytomegalovirus (CMV), and Epstein–Barr virus (EBV) as well as Toxoplasma gondii was determined in childhood (age 11 years) in 395 sons and 174 daughters of fathers with or without SUD. Its relationships with a cognitive characteristic (IQ) in childhood and with risk for SUD in adulthood were examined using correlation, regression, survival, and path analyses. Exposure to HSV-1, EBV, and T. gondii in males and females, and CMV in males, was associated with lower IQ. Independent of that relationship, EBV in females and possibly in males, and CMV and possibly HSV-1 in females were associated with elevated risk for SUD. Therefore, childhood neurotropic infections may influence cognitive development and risk for behavior disorders such as SUD. The results may point to new avenues for alleviating cognitive impairment and SUD risk.